The Role of the Electrode Surface in Na–Air Batteries: Insights in Electrochemical Product Formation and Chemical Growth of NaO2. Issue 4 (25th September 2017) - Lutz, Lukas; Corte, Daniel Alves Dalla; Chen, Yuhui; Batuk, Dmitry; Johnson, Lee R.; Abakumov, Artem; Yate, Luis; Azaceta, Eneko; Bruce, Peter G.; Tarascon, Jean‐Marie; Grimaud, Alexis
Abstract: The Na–air battery, because of its high energy density and low charging overpotential, is a promising candidate for low‐cost energy storage, hence leading to intensive research. However, to achieve such a battery, the role of the positive electrode material in the discharge process must be understood. This issue is herein addressed by exploring the electrochemical reduction of oxygen, as well as the chemical formation and precipitation of NaO2 using different electrodes. Whereas a minor influence of the electrode surface is demonstrated on the electrochemical formation of NaO2, a strong dependence of the subsequent chemical precipitation of NaO2 is identified. In the origin, this effect stems from the surface energy and O2 /O2 − affinity of the electrode. The strong interaction of Au with O2 /O2 − increases the nucleation rate and leads to an altered growth process when compared to C surfaces. Consequently, thin (3 µm) flakes of NaO2 are found on Au, whereas on C large cubes (10 µm) of NaO2 are formed. This has significant impact on the cell performance and leads to four times higher capacity when C electrodes with low surface energy and O2 /O2 − affinity are used. It is hoped that these findings will enable the design of new positive electrode materials with optimized surfaces. Abstract : In NaO2 batteries, the chemical crystallization (growth) of NaO2 is highly sensitive to the surface energy and O2 /O2 − affinity of the electrode. On gold, strong interaction with O2 − leads to formation of small NaO2 flakes, while on carbon (low surface energy) large NaO2 cubes are found. This has significant impact on the cell performance.